Impact of intellectual capital on organizational performance: Evidence from a developing country - Barkat, Waseem (Allied Business Academies, 2018)
Intellectual capital has been much discussed in developed nations for organization's value creation. In a competitive market, intellectual capital proved to be a source of a competitive advantage for organizations. However, this study is conducted to anticipate the potential effect of intellectual capital in the context of a developing country. The central objective of this research is to hypothesize the mediation effect of knowledge process capability between intellectual capital dimensions and organizational performance. Survey method is applied for data collection. Data is collected from 154 large manufacturing industries in Pakistan. The analysis is performed via partial least square (WarpPLS 5.0). The outcome of this research revealed that knowledge process capability mediates with all dimensions of intellectual capital. Among the dimensions of intellectual capital, relational capital has the strongest effect on knowledge process capability and organizational performance. The present study advances knowledge by applying intellectual capital effects on organizational performance in a developing country. This study added new insights for the HR managers and policy makers of developing countries to disseminate such concepts to their respective organizations.